Study and Analytical Modeling of the Influence of Technological and Geometric Parameters on the Performance of Ga0:67In0:33P=GaAs=Ga0:70In0:30As Tri-junction Photovoltaic Solar Cells - AGBOMAHENA; NDORERE, Nicodeme (My University, 2020)
cells with high efficiency. Efforts are being made to increase the efficiency of solar cells and reduce their cost of production. In order to optimize the performance of multi-junction solar cells, this paper presents an analytical model allowing to study and model the influence of technological and geometric parameters on the performance of tri-junction solar cells Ga0:67In0:33P=GaAs=Ga0:70In0:30As. These parameters are the thickness, doping and Gap energy of the three sub-cells making up the tri-junction solar structure. The thicknesses and doping of the emitters (bases) of the sub-cells are varied and *Corresponding E-mail: ndoreregity@gmail.com; cells with high efficiency. Efforts are being made to increase the efficiency of solar cells and reduce their cost of production. In order to optimize the performance of multi-junction solar cells, this paper presents an analytical model allowing to study and model the influence of technological and geometric parameters on the performance of tri-junction solar cells Ga0:67In0:33P=GaAs=Ga0:70In0:30As. These parameters are the thickness, doping and Gap energy of the three sub-cells making up the tri-junction solar structure. The thicknesses and doping of the emitters (bases) of the sub-cells are varied and
Keywords: Tri-junction solar cell; Doping; thickeness; emitter; base